Chemical Analysis and Therapeutic Uses of Ginger (Zingiber officinale Rosc.) Essential Oil: A Review. Issue 4 (4th July 2018) - Munda, Sunita; Dutta, Sukriti; Haldar, Saikat; Lal, Mohan
Abstract: Ginger is a medicinal plant that has been used traditionally in Ayurvedic, Chinese and Tibb- Unani herbal drugs since ancient times. Now-a-days ginger oil is commercially produced from dry or fresh ginger rhizome. Systematic study of the oil from different cultivars resulted in various chemical constituents present in different proportions which are of immense therapeutic uses and are of high commercial interest. The different studies can be performed using GC, GC-MS and supercritical fluid extraction process. Zingiberene, ar- curcumene, citral, β-bisabolene, geranial, camphene are the major active compounds present in ginger essential oil. The GC-MS oil analysis showed abundancy in oxygenated compounds. This quality may be attributed to the antimicrobial activity of the ginger oil. The ginger oil also has high therapeutic values such as anti- inflammatory, analgesic, anticancer, antioxidant, antinociceptive, antitussive properties etc. Moreover many advanced techniques developed so far led to the discovery of different cultivars of ginger with different and improved oil yielding capacity. Many researches are still going on the chemical analysis and therapeutic uses of the ginger essential oil so in this review an attempt is being made to provide up-to-date information on the therapeutic studies and essential oil composition.